Socialization to the Society to Achieve Safe, Peaceful, Qualified, and Dignitarian Elections in 2024 - Wardani, Anita; Daliman, Daliman; Hidayah, Nur; Masbait, Sarjun (International Journal of Public Devotion, 2024)
General elections are essentially a means of people's sovereignty, so that none of the nations in the world that recognize themselves as democratic states hold a general election, in other words, a compulsory general election is held in a country that has a democratic system. To create a secure, peaceful, quality, and integrity general election, the whole of society must be involved in it, the people must be more intelligent in sorting out the hoaks, free from hate speech and rejecting money politics.In order to realize a safe, peaceful, quality and dignified electoral process, the Islamic Institute of Mamba’ul Ulum Surakarta cooperates with the village of Jelobo, Klaten district through socialization activities. As for the outcome of this socialization activity, the participants' understanding of the Safe, Peaceful, Qualified and Dignity General Election has an average score of 76%.